Optimization of US Soybean Meal for Growth Performance of Tilapia (Oreochromis niloticus) Compared to Commercial Feed on Lake Toba, North Sumatera, Indonesia - Juanda; djamil, Hasim; Saragih, Friska Setiawani; Susanti, Apryani (Department of Aquaculture, 2025)
Feed is the most important factor in supporting the growth of tilapia fish production. Soybean meal is recognized as a cost-effective alternative protein source to replace costly fish meal in aquaculture. This study aimed to evaluate and compare the growth performance of tilapia (Oreochromis niloticus) fed a diet optimized with US soybean meal compared to an available commercial tilapia diet in fish farming in Lake Toba, North Sumatra. Two experimental diets were used including commercial feed as a control and feed with optimized US Soybean meal with three replications. The experimental diets were given two times a day. After 240 days of feeding, data from the study were analyzed using independent samples T-test on the Statistical Product and Service Solutions (SPSS) software version 25.0. The Survival Rate (SR), Average Body Weight (ABW), Feed Conversion Ratio (FCR), and the harvested biomass of tilapia on the feed with US Soy were 64.2%, 1262.2 g, 1.76, and 244.144 kg, respectively. There was no significant effect (P > 0.05) on the SR (Survival rate), Feed Conversion Ratio (FCR), ADG (Average Daily Growth), and final ABW (Average Body Weight) in both the experimental diets. However, the harvested biomass of tilapia, fed with feed-optimized US soybean meal was better than control. An important finding of this research is the potential of optimizing US soybean meal in aquafeed to increase the growth of tilapia farming.